Stress hyperglycemia ratio and risk of incident myocardial infarction in the general population: a large-scale cohort study - Wenke Cheng; Xianlin Zhang; Jiqian Shi; Huaiyu Ruan; Pinfang Kang; Hongyan Sun; Meiyang Xu; Zhongyan Du; Bi Tang (Frontiers in Nutrition)
BackgroundStress hyperglycemia ratio (SHR), which combines acute admission glucose with chronic glycemic indices, is a novel marker of stress hyperglycemia. Its association with acute myocardial infarction (AMI) risk in the general population remains unclear.MethodsThis prospective cohort study used data from the UK Biobank and included 337,620 participants without known cardiovascular disease (CVD). SHR was calculated as admission glucose/[(28.7 × HbA1c%) – 46.7], with levels categorized into quintiles. The primary outcome was incident AMI, while ST-segment elevation myocardial infarction (STEMI) and non-ST-segment elevation myocardial infarction (NSTEMI) were evaluated as secondary outcomes. Cox proportional hazards models assessed the relationship between SHR and incident AMI risk. An accelerated failure time model was used to evaluate the effect of SHR on time to AMI onset, and dynamic changes in SHR were analyzed using a restricted cubic spline (RCS).ResultsDuring a median follow-up of 164.8 months (IQR: 155.7–173.6), 10,598 AMI events, including 3,019 STEMI and 5,711 NSTEMI cases, were recorded. Compared with the fourth quintile, the first, second, and third quintiles had increased AMI risks by 19% (HR 1.19; 95% CI 1.12–1.27), 16% (HR 1.16; 95% CI 1.09–1.24), and 7% (HR 1.07; 95% CI 1.00–1.14), respectively, with no significant increase observed in the highest quintile. RCS analysis revealed a U-shaped relationship between SHR and incident AMI risk (P for non-linearity < 0.001), with the lowest risk at an SHR of 0.966.ConclusionIn the general population without known CVD, SHR exhibited a U-shaped association with incident AMI risk, with the lowest risk observed at an SHR of 0.966, particularly at levels below this threshold.